2019
DOI: 10.1155/2019/4592462
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mask Type on the Effectiveness of and Adherence to Unattended Home-Based CPAP Titration

Abstract: Objectives. To compare interfaces performance during home-based automatic titration (APAP). Methods. Retrospective study based on APAP titration from Obstructive Sleep Apnea Syndrome (OSA) patients. Results. 707 patients, 513 men (70.6%), were titrated. Masks were 104 pillows (14.7%), group I (GI); 532 nasal (75.2%), group II (GII); and 71 oronasal masks (10%), group III (GIII). We found differences in effective pressure to the device (P90/P95) (GI: 7.13±1.9 vs. GII: 8.3±2.1 vs. GIII: 9.3±2.6 cmH2O, p <0.00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 33 publications
(31 reference statements)
0
13
0
8
Order By: Relevance
“…OSA is associated with increased fatigue, somnolence, headaches, depression, and decreased quality of life, as well as higher risks of metabolic disease, cardiovascular disease, and motor vehicle accidents 5,6 . Treatment options for OSA include weight loss, oral appliances, surgical procedures, and positive airway pressure (PAP) therapy, 1,5 among these options, PAP is the treatment of choice for patients with moderate to severe OSA 1,7 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…OSA is associated with increased fatigue, somnolence, headaches, depression, and decreased quality of life, as well as higher risks of metabolic disease, cardiovascular disease, and motor vehicle accidents 5,6 . Treatment options for OSA include weight loss, oral appliances, surgical procedures, and positive airway pressure (PAP) therapy, 1,5 among these options, PAP is the treatment of choice for patients with moderate to severe OSA 1,7 …”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors affect adherence to PAP, including the patients, their families, their physicians, other healthcare professionals, healthcare facilities, and governmental policies; all of these play important roles, in addition to the more commonly emphasized equipment and personality factors 2 . The impact of the severity of this disease cannot be overlooked 9 ; it has been reported that PAP adherence ranges from 40% to 80% 7 . Therefore, achieving good adherence to PAP is a well‐recognized clinical goal for the management of OSA 10 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Continuous positive airway pressure (CPAP) therapy is the best available treatment for moderate (AHI [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] to severe OSA (AHI >30), and with CPAP treatment the AHI should be normalised. [8][9][10][11][12] CPAP treatment may be administered with a nasal mask, nasal pillows or an oronasal mask.…”
Section: Introductionmentioning
confidence: 99%